2020
DOI: 10.7759/cureus.8095
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors in Lung Cancer: Role of Biomarkers and Combination Therapies

Abstract: Lung cancer is the leading cause of cancer-related death worldwide, with a poor prognosis. Despite aggressive treatment, progression-free survival (PFS) and overall survival are limited. Recently, various kinds of immune checkpoint inhibitors (ICIs) have emerged for several cancers, targeting PD1, PDL1, and CTLA-4. ICIs have made a significant breakthrough in cancer and revolutionized the management of cancer including lung cancer. However, there are a lot of controversies regarding which group of patients is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Besides PD-L1 expression, TMB, DNA mismatch repair deficiency, extent of CD8+ cell infiltration, immune gene expression signatures and composition of the gut microbiome have also been proposed to correlate with clinical response to anti-PD-1/PD-L1 ICIs (29)(30)(31)(32). NSCLC patients with high TMB and the smokers were found to respond better to anti-PD-1/PD-L1 ICIs (33).…”
Section: Predictive Biomarkers For Selecting Nsclc Patients For Immunotherapymentioning
confidence: 99%
“…Besides PD-L1 expression, TMB, DNA mismatch repair deficiency, extent of CD8+ cell infiltration, immune gene expression signatures and composition of the gut microbiome have also been proposed to correlate with clinical response to anti-PD-1/PD-L1 ICIs (29)(30)(31)(32). NSCLC patients with high TMB and the smokers were found to respond better to anti-PD-1/PD-L1 ICIs (33).…”
Section: Predictive Biomarkers For Selecting Nsclc Patients For Immunotherapymentioning
confidence: 99%
“…Surgery combined with preoperative adjuvant therapy has been the mainstay of treatment for patients with advanced stage NSCLC, 4 but complete resection is affected by the size and location of the tumor. There is a critical need to develop better therapeutic approaches to treat patients with locally advanced stage disease 5 . Increasing numbers of guidelines recommend targeted or adjuvant immunotherapy for patients with locally advanced NSCLC in order to maximize benefit to patients 6 …”
Section: Introductionmentioning
confidence: 99%
“…As few studies have analysed the efficiency and safety of ICI treatment in patients with SCLC, and no comparison directly included patients with SCLC versus those with NSCLC, to a certain extent, we bridged the gap in efficiency and safety data for ICI therapy among patients with NSCLC and SCLC. Previously, Maung et al have shown that ICIs conferred better survival benefits than chemotherapy in both NSCLC and SCLC [ 53 ]. However, their conclusions were mainly based on qualitative analysis, without data analysis of clinical trials.…”
Section: Discussionmentioning
confidence: 99%